The MeatEater guide to wilderness skills and survival - Rinella, Steven (Random House, 2020)
"For anyone actually spending time outside, The MeatEater Guide to Wilderness Skills and Survival is the perfect antidote to the sensationalism of today, filled instead with advice you'll actually use. Along with lessons from the real-life experiences of renowned outdoors expert and host of the Netflix Original Series MeatEater Steven Rinella, its pages are packed with tried-and-true tips, techniques, and gear recommendations from Rinella and his trusted crew of expert hunters, anglers, emergency room doctors, climbers, paddlers, and wilderness guides who've learned from their own mistakes. Among other skills, readers will learn about old-school navigation and essential satellite tools, how to build a basic first-aid kit and apply tourniquets, how to repel grizzly bear charges, and how to effectively purify water using everything from ancient methods to cutting edge technologies. This essential guide delivers the hard-won insights and know-how, garnered from Rinella's own experiences and mistakes, that will make any reader feel comfortable and competent while out in the wild. Throughout, survival stories will highlight the real dangers that can arise in nature, from hypothermia and frostbite to encounters with the world's most dangerous animal--the mosquito"--